The Influence of Training and Motivation on Employee Performance with Perfomance Appraisal as an Intervening Variable - Setyowati, Denny; Tridayanti, Hermien; Suyono, Joko; Kurnia, Ratna Diah; Ardiansyah, Herwin (Universitas Muhammadiyah Gresik, 2024)
This research aims to determine the influence of training and work motivation variables which have an influence on employee performance with performance appraisal as an intervening variable. The methodological design in this research is to use quantitative methods and approaches. The population in this research is all 34 fitness industry employees in sidoarjo. The sampling technique in this research is a saturated sample.the data analysis method uses smartpls version 3. Findings the results of this study state that job training and job appraisals have a significant influence on employee performance, work motivation has no significant influence on employee performance, job training and work motivation have a significant influence on job appraisals, job training and work motivation have a significant influence on employee performance with job appraisals as an intervening variable.